Proceedings of the 8th ACM International Symposium on Pervasive Displays 2019
DOI: 10.1145/3321335.3324931
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and perceptions of interactive location-tracking displays

Abstract: Tracking the location of people and their mobile devices creates opportunities for new and exciting ways of interacting with public technology. For instance, users can transfer content from public displays to their mobile device without touching it, because location tracking allows automatic recognition of the target device. However, many uncertainties remain regarding how users feel about interactive displays that track them and their mobile devices, and whether their experiences vary based on the setting. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…One recent study found that people showed favorable response to adopt novel location-tracking systems (e.g. SimSense) as long as the system is transparent about its data collection and ownership and reflects users' tracking preferences [9].…”
Section: Introductionmentioning
confidence: 99%
“…One recent study found that people showed favorable response to adopt novel location-tracking systems (e.g. SimSense) as long as the system is transparent about its data collection and ownership and reflects users' tracking preferences [9].…”
Section: Introductionmentioning
confidence: 99%